Influence of service quality and marketing mix on customer satisfaction with online bank partners - Pebiansyah, Ade Oki; Sulaeman, Lambok Rommy; Utama, Deni; khoirun nisa, Salsabila (Enrichment : Journal of Management, 2024)
Business competition in this era of globalization and industrial revolution 4.0 develop recently quickly and more competitive. Especially in Payment Point Online Bank (PPOB) industry that currently having a wide market. The Collect Agent should foster innovation and enhance creativity to encourage repeat transactions from customers at the Payment Point Online Bank (PPOB) company. This research aims to review and analyze the impact of service quality and marketing mix on the customer satisfaction of PT. XYZ's partners. This research employs both descriptive and verificative approaches based on the dependent variable being studied. The descriptive research provides an overview of the service quality at XYZ Company in Bandung, focusing on customer satisfaction levels. Conversely, the verificative aspect aims to test the hypothesis derived from field data collection. Through this research, we will assess and critically evaluate whether there is an influence of service quality and marketing mix on customer satisfaction at XYZ Company in Bandung. Service quality in partial can influences customer satisfaction. Promotional Mix in partial can influences customer satisfaction, Kualitas Pelayanan and Promotional Mix simultaneously had an influence on customer satisfaction , with the percentage the influence of as much as 68,7 %.